Performance evaluation of reverse logistics: A case of LPG agency - Kottala Sri Yogi; Tahir Nisar (Cogent Business & Management, 2015)
Majority of the manufacturing companies are incorporating the practice of reverse logistics in their value chain. In manufacturing processes, the concept of reverse logistics plays a vital role in enhancing the company's profit margin for sustainable business growth. For every company, there is a need of performance measurement system to be established as successful business tool. However to predict better results, how smartly the inputs for the transformation or business process are being effectively and efficiently used has to be analyzed. Drawing attention to the growing popularity in adapting the best practices of reverse logistics among different manufacturing industries, this paper aims to build a methodology in order to measure the performance of liquefied petroleum gas (LPG) agencies. To do so, it has undertaken the Asian emerging market-India as a case study and improved the understanding of performance measurement in reverse logistics to refilling LPG cylinders. Further, it has suggested a framework affecting the implementation of reverse logistics activities and its network.
Keywords: 650